2009
DOI: 10.1037/a0014665
|View full text |Cite
|
Sign up to set email alerts
|

Strong claims and weak evidence: Reassessing the predictive validity of the IAT.

Abstract: The authors reanalyzed data from 2 influential studies-A. R. McConnell and J. M. Leibold (2001) and J. C. Ziegert and P. J. Hanges (2005)-that explore links between implicit bias and discriminatory behavior and that have been invoked to support strong claims about the predictive validity of the Implicit Association Test. In both of these studies, the inclusion of race Implicit Association Test scores in regression models reduced prediction errors by only tiny amounts, and Implicit Association Test scores did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
242
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(264 citation statements)
references
References 73 publications
(200 reference statements)
7
242
3
Order By: Relevance
“…
We respond to a critique by H. Blanton et al (2009), challenging our previous work demonstrating that an Implicit Association Test designed to assess implicit prejudice reliably predicts intergroup discrimination (A. R. McConnell & J. M. Leibold, 2001). We outline 3 flawed aspects of the critique.
…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…
We respond to a critique by H. Blanton et al (2009), challenging our previous work demonstrating that an Implicit Association Test designed to assess implicit prejudice reliably predicts intergroup discrimination (A. R. McConnell & J. M. Leibold, 2001). We outline 3 flawed aspects of the critique.
…”
mentioning
confidence: 91%
“…We are pleased to offer our thoughts on the Blanton et al (2009) article. In July 2006, we were contacted by an author on that article (G. Mitchell, personal communication, July 25, 2006), who asked us for copies of the data sets for our publication, McConnell and Leibold (2001).…”
Section: Prefacementioning
confidence: 99%
See 1 more Smart Citation
“…This is by no means universally accepted in the psychological literature; indeed it is currently the subject of much quite heated debate (see Blanton et al, 2006Blanton et al, , 2007Blanton et al, , 2009 for a critique of this position and Greenwald, Nosek and Sriram, 2006, McConnell and Leibold, 2009, and Ziegert and Hanges, 2009 for some rebuttals). However, it would seem that in some domains, this notion of implicit attitudes, deriving from various associative connections and operating unconsciously alongside our more reflective attitudes (and indeed conflicting with them on occasion), might have some credibility (Beattie, 2013: Kahneman, 2011.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not address the predictive validity of the IRAP, a crucial test of the value of any measure. Race IATs have been shown to predict laboratory examples of discriminatory behavior (e.g., Green, et al, 2007;Heider & Skowronski, 2007), although some recent meta-analyses have suggested that the predictive validity data as a whole is relatively unimpressive (Blanton, et al, 2009;Oswald, Mitchell, Blanton, Jaccard, & Tetlock, 2013). It seems important to subject the IRAP to an examination of predictive validity, given the divergence in methodology from the IAT and the more specificity of results it can provide.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%